Whole-body magnetic resonance imaging findings and patterns of chronic nonbacterial osteomyelitis in a series of Greek pediatric patients. (3rd June 2022) - Papakonstantinou, Olympia; Prountzos, Spyridon; Karavasilis, Eustratios; Atsali, Erato; Bizimi, Vasiliki; Alexopoulou, Efthymia; Fotis, Lampros
Background: Chronic nonbacterial osteomyelitis (CNO) is a pediatric autoinflammatory disorder presenting with sterile inflammatory bone lesions. Whole-body MRI (WBMRI) has most recently emerged for disease assessment, but data are limited. Purpose: The purpose is to evaluate the imaging findings and patterns of CNO on WBMRI in a series of Greek pediatric patients. Material and Methods: Whole-body magnetic resonance imaging studies of all children with documented CNO, performed in a single tertiary center, were retrospectively reviewed. WBMRI included coronal T1 and short-tau inversion recovery (STIR), whole spine sagittal STIR, and ankle/foot sagittal STIR images. High signal intensity lesions on STIR images corresponding to bone marrow edema were recorded. The SPSS v.20 statistical package was used for descriptive statistics. Results: Twenty children were included (mean age: 12, range: 6–16 years) with 1–31 lesions (mean: 11.8) on WBMRI. Two children had unifocal disease localized at the clavicle, three paucifocal (1–4 lesions), and 15 multifocal bone involvement. All but two children presented with ankle pain and exhibited lesions at the bones of the ankle joint (90%) followed by the knee (50%) and pelvis (10%). The tibia was the most frequently affected bone (70%) followed by calcaneus (60%), fibula (50%), femur (45%), talus, and metatarsals (45%). No lesions in the cervical, thoracic, lumbar spine, and mandible were documented. Only small sacral lesions were seen in 25% of patients with the extensive peripheral disease. Bilateral metaphyseal and epiphyseal involvement with transphyseal extension were common, but the periosteal reaction and well-defined lesion margins were rare. Conclusion: Frequent involvement of the foot and ankle and paucity of substantial spinal involvement were seen in Greek pediatric patients with CNO.